Islam, the Islamic worldview and Islamic economics - Haneef, Mohamed Aslam (International Islamic University Malaysia, 1997)
A correct understanding of the fundamental elements in the Islamic economic vision is a pre-requisite for the development of Islamic economics. This article begins by putting forward a conceptual understanding of these fundamental elements which include the nature of man, the universe and the concept of din. The article argues that due to differences in the Islamic economic vision to those of western economics, coupled with the epistemological and methodological framework in Islamic scholarship, the development of Islamic economic thought (and consequently policy prescriptions) differs. While internal logic, coherence and consistency are necessary conditions for scientific exposition, Islamic economics should be evaluated within its own framework and using its own criteria. Within acceptable parameters determined by revelation, this paper also argues that varying opinions in economics are possible and probable.